Ocular allergy and keratoconus - Namrata Sharma; Kavita Rao; Prafulla K Maharana; Rasik B Vajpayee (Indian Journal of Ophthalmology, 2013)
Keratoconus is the most common corneal ectatic disorder, the cause of which is largely unknown. Many factors have been implicated, and the ocular allergy is being one of them. The commonly proposed pathogenesis includes the release of inflammatory mediators due to eye rubbing which may alter the corneal collagen and lead to corneal ectasias. The onset of keratoconus is often early in cases associated with allergy and routine corneal topography may detect subtle forms of keratoconus. These cases may require early keratoplasty and are at an increased risk of having acute corneal hydrops. Surgical outcomes are similar to primary keratoconus cases. However, post-operative epithelial breakdown may be a problem in these cases. Control of allergy and eye rubbing is the best measure to prevent corneal ectasias in cases of ocular allergy.